Pile Foundation Problems and Reinforcement Techniques in Highway Bridge Engineering - Li, Wei (Journal of Theory and Practice of Management Science, 2023)
The construction of road and bridge pile foundations is a complex system engineering that involves many construction links. There are many common problems that can have a significant impact on the overall quality of road and bridge pile foundation construction. Therefore, it is necessary to face the quality issues of road and bridge pile foundations and take corresponding technical measures to strengthen the stability and safety of the bridge. The article discusses common pile foundation problems and reinforcement techniques in road and bridge engineering.